The Application of Acoustic Material Egg Tray as Noise Absorbers in the Interior of Elementary School Classroom - Asri A. Muhammad; Astuti Salim; Firdawaty Marasabessy (Institute for Research and Community Services, 2017)
The classroom needs a comfortable atmosphere for learning activities. One of the comfortable factors is free from noise, which was not present in the classrooms of SDN 4 in Ternate City. This happens because the school is located on the main street with two lanes for two directions. The noise level at this location measured from the front classroom, which is directly adjacent to the main road, reached 74,02 dB. The number exceeds the noise threshold for the educational environment, which may prevent the learning activities from running optimally, as well may cause the students and teachers loss of hearing. The present community service attempted to utilize used goods in the form of egg trays to reduce waste in the environment. The KKN-PKM aimed to renovate the classroom so that it becomes a soundproof classroom by reducing the noise from the outside of the building to make the students and teachers in the classroom feel comfortable during the learning activities. The methods used in the early stage were surveys, interviews, and measurements of the beginning and end. The result of this community service was in the form of a soundproof classroom of SDN 4 in Ternate City. The average number of measurements before and after the installation of egg trays looked significant, that is 74,02 dB was reduced to 59,8 dB. The result obtained a positive response from the stakeholders and all the students and teachers of SDN 4 in Ternate City.